Finite Element Analysis Of Hydraulic Bulging Of Metal Tubes - Na'mi, Saleem (2006)
The use of finite element simulation in the development of bulge forming procedures is becoming more important as it provides a cheap and efficient way to determine important process parameters. Further improvements to the bulge forming method will be realized with the use of simulation and the design of advanced tooling. One major area where tube hydro forming is applied is in automotive structures. In this current research, numerical analysis was conducted using the explicit finite element code ANSYS 2D. One-fourth model of the whole geometry consisting of the tube and the dies was adopted in consideration for symmetric property of the tube deformation. The model of metal tube is assumed as a bilinear isotropic model approximating the characteristics of annealed mild steel was adopted as the material for the tube. The final model contains 630 nodes and 560 elements included 19 contact elements between die and tube. The interface between the die and the tube was modeled using an automatic node to surface contact.